2020
DOI: 10.1111/jocn.15293
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to hand hygiene in critical sectors: Can we go on like this?

Abstract: Aims and objectives The rates of healthcare‐associated infections are high around the world. Hand hygiene is considered the most effective measure to reduce the transmission of pathogens in the hospital environment. Our objective was to evaluate adherence to hand hygiene in critical units of a tertiary‐level hospital in Central‐West Brazil. Design Observational study employing cross‐sectional data. Reporting rigour was demonstrated using the STROBE checklist. Methods Observation of hand hygiene practices of 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
2
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 23 publications
0
19
2
10
Order By: Relevance
“…In our study, the most prevalent correct practice was related to hand washing as only 5% of our participants rarely apply proper hand washing, while 58.5% of them always apply it properly. This is higher than that has been found in a study conducted in Brazil as the hand washing adherence rate was 46.25% in critical care unit [31] About 58.5.5% of the studied group always wears PPE, while only 8.2% rarely wears it properly and 23% always Uses N95 mask during all patient management procedures, this is in line with a study conducted in Saudi Arabia which has reported that 71% of health workers wear the mask during work [32]. Another study that has been carried out in Pakistan has shown that the correct usage of masks was good in 35.2%, moderate in 45.4%, and poor in 19.3% of the studied group [33].In contrast, a study has been carried out in Vietnam has reported that there is a limited number of correct responses regarding items related to the use of personal protective equipment [34].…”
Section: Discussioncontrasting
confidence: 74%
“…In our study, the most prevalent correct practice was related to hand washing as only 5% of our participants rarely apply proper hand washing, while 58.5% of them always apply it properly. This is higher than that has been found in a study conducted in Brazil as the hand washing adherence rate was 46.25% in critical care unit [31] About 58.5.5% of the studied group always wears PPE, while only 8.2% rarely wears it properly and 23% always Uses N95 mask during all patient management procedures, this is in line with a study conducted in Saudi Arabia which has reported that 71% of health workers wear the mask during work [32]. Another study that has been carried out in Pakistan has shown that the correct usage of masks was good in 35.2%, moderate in 45.4%, and poor in 19.3% of the studied group [33].In contrast, a study has been carried out in Vietnam has reported that there is a limited number of correct responses regarding items related to the use of personal protective equipment [34].…”
Section: Discussioncontrasting
confidence: 74%
“…Although it has been suggested that correct hand hygiene practices are not widely followed by health professionals (46.3% rate of adherence) [18], our results suggest that professionals at our hospital are more aware of preventive hand hygiene measures than the correct use of masks. Nevertheless, self-use of masks when respiratory symptoms (coughing, sneezing) are present, and the use of masks from the moment of first contact for patients with the same symptoms have been classically considered universal or standard precautions [19].…”
Section: Preventive Behaviours Before the Pandemiccontrasting
confidence: 69%
“…As nurses, we are aware that handwashing has not always been taken as seriously as it should, with compliance and adherence in clinical settings far from optimal over time (Bezerra et al, 2020;Pittet, 2001). Multiple reports from different countries have shown that hand hygiene compliance rate has been estimated at only 40% (Erasmus et al, 2010) while the rate of adherence in critical care units was only 46.25% (Bezerra et al, 2020). Although this is a simple and lifesaving task, it is not, regrettably, always undertaken (Doronina, Jones, Martello, Biron, & Lavoie-Tremblay, 2017).…”
mentioning
confidence: 99%